Using the Two-Phase Emission Detector RED-100 at NPP to Study Coherent Elastic Neutrinos Scattering off Nuclei - RED-100 Collaboration (Physics, 2023)
The two-phase emission detector RED-100 with 130 kg of liquid xenon as a working medium has been exhibited at a distance of 19 m from the core of the VVER-1000/320 nuclear power reactor at the fourth power unit of the Kalinin Nuclear Plant Power in 2021–2022. Due to the high sensitivity of the detector for weak ionization signals (down to single electrons), the detector has been used to search for the elastic coherent scattering of reactor electron antineutrinos off xenon nuclei. However, the observation of ~30 kHz single-electron noise did not quite allow for an effective selection of the useful events. The next experiment with the RED-100 detector is considered to be arranged with 62 kg of liquid argon as a working medium. The advantages of this approach are discussed in this paper.